IDEOLOGI DALAM IKLAN - Arif Agung Suwasono (Ars: Jurnal Seni Rupa dan Desain, 2007)
This paper discusses the ideology implied in an advertisement. The discussion does not focus uponthe busi» uf the ideology und its schools, but instead on how an advertisement acts as a means o f capitalism./\s the media o f an ideology, an advertisement not only reflects reality but also represents the social realitythat often transforms ideological meaning. As a social representation, an advertisement is a language,covered by an accumulation o f values, choices and interests which are integrated within the capitalist systemand which eventually fosters the development o f consumerism.Keywords: ideology, advertisement, capitalism.